Living Longer, Living Better – Exploring the Heart-Mind Connection - by Lionel Opie - Przybojewski, Jerzy Zbigniew (SA Heart Journal, 2017)
Professor Lionel H. Opie has produced a work of genius in the form of this, his latest book. “Living Longer, Living Better – Exploring the Heart-Mind Connection” truly deserves the iconic status which two of his other books, “Drugs for the Heart”, 7th Edition (co-edited with Bernard J. Gersh) and “Heart Physiology: From Cell to Circulation”, 4th Edition, have achieved. I cannot help but fully agree with Professor Timothy Noakes’ comment in his foreword to the book, “I know of no one who understands the heart more completely or who can express himself with greater effect to any audience than can Lionel”.